METHODS OF DEVELOPING COMMUNICATIVE COMPETENCE THROUGH LINGUO-CULTURAL APPROACH. - Yoʻldosheva Mardona Oʻktam qizi; Kenjaeva Mukhlisa Bakhodir qizi (TADQIQOTLAR.UZ, 2024)
ABSTRACT: Linguocultural approach involves the formation of linguocultural competence that is a system of both knowledge and skills about the culture and the ability to use them in a particular communicative situation.The prerequisite for communicative competence is to build motivation. Practice shows that visual displays, discussions, student project activities, games, and especially role-playing in higher- level classes contribute to motivation. Students can easily express their views using vocabulary learned through visual aids.